Rancang Bangun Aplikasi Monitoring Tumbuh Kembang Anak Balita Pada Posyandu Kelurahan Duren Sawit - Junaidi; Elmi Devia; Mega Wahyu Rhamadani; Wargijono Utomo (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Children are one of the valuable assets for a family. Children's growth and development can run well if their nutritional needs are met. Stunting is one of the disorders caused by poor parenting practices. Lack of parental knowledge about child growth and development can increase the risk of stunting. Duren Sawit Village is a village located in Duren Sawit District, East Jakarta Administrative City, DKI Jakarta Province. From interviews conducted with sources at the RW. 015 Posyandu, Duren Sawit Village, it is known that the process of recording child growth and development data is still done manually by recording child data in the Maternal and Child Health (KIA) record book. Based on the statement above, we are interested in creating an application for monitoring the growth and development of toddlers at the RW. 015 Posyandu, Duren Sawit Village, to make it easier for Posyandu cadres to send toddler nutritional status data to the Duren Sawit Sub-dept.